Teachers' Perception of Interactive Video-Based Learning Media in Lampung Language Script Material for Grade 2 Elementary School - Awanda, Ifan; Yustikasari, Miranda; Uminar, Ajeng Ninda; Sari, Tri Maya (LinguaScopes: International Journal of Language Education, 2024)
This study analyses teachers' opinions of interactive video-based learning media for teaching the Lampung language script to Grade 2 elementary school students in the Negeri Katon District, Pesawaran. Using a descriptive qualitative technique, data were acquired through semi-structured interviews and classroom observations with selected Lampung language teachers. The findings demonstrate that while teachers accept the benefits of interactive media—such as higher student engagement and enhanced retention—several challenges restrict its effective implementation, including limited access to resources, inadequate training, and infrastructural limits. The study underlines the significance of targeted professional development and technology support to increase the incorporation of these tools into regional language education. By addressing these limitations, interactive video-based learning has the potential to play a crucial role in revitalizing the Lampung language and fostering cultural preservation.